Ti-B-N high-toughness wear-resistant ceramic coating as well as preparation method and application thereof
By introducing nanotwin structures and high-strength covalent bonds into the ceramic coating, the problem of high hardness but poor wear resistance in the prior art is solved, and the high strength and high toughness of the ceramic coating are achieved, which significantly improves its wear resistance and impact resistance.
Patent Information
- Application Number
- CN202411568645.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, metal coatings have high hardness but poor wear resistance and insufficient toughness, making it difficult to meet the requirements of the nuclear power service environment.
Ti-B-N ceramic coating is prepared by magnetron sputtering technology to regulate the atomic proportion of B and nanotwin volume fraction in the ceramic coating to form high-strength covalent bonds and nanotwin structures to improve the hardness and toughness of the coating.
The wear resistance and impact resistance of ceramic coatings are significantly improved, the wear mechanism is transformed into uniform wear, and the hardness and toughness of the coating are improved, which is suitable for high-demand applications such as nuclear power rotating components.
Smart Images

Figure CN119753593A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic coating preparation, and in particular to a Ti-BN high-strength, toughness, and wear-resistant ceramic coating and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern industry, wear and failure have become an important problem threatening the service life of engineering equipment in many engineering fields. According to incomplete statistics, from 1996 to 2021, the rotating parts of CGN Group, such as pump shafts, impellers, and valve stems, had wear problems more than 10,000 times. Insufficient wear resistance on the surface of components is the main cause of component failure, which will lead to a sharp shortening of the service life of components and increase the cost of maintenance and replacement. Surface protection is an effective way to improve the hardness and wear resistance of materials without changing the base material, such as hard wear-resistant coating technology. In view of the wear and failure of rotating parts in nuclear power plants, the development of hard wear-resistant coatings is a powerful and effective way to slow down the surface wear of workpieces. To improve the wear resistance of coatings, the key is to increase the hardness and toughness of coatings and reduce the elastic modulus and friction coefficient of coatings. At present, there have been some research and development related to hard coatings, such as multi-component composite coatings TiAlN, CrAlN, TiCrAlN, etc., whose hardness can generally reach 30-50GPa. The Chinese patent with publication number CN115181948A uses DC magnetron sputtering technology to prepare W-Si-B hard coatings, which can reach a hardness of more than 35GPa and have good tribological properties (wear rate as low as 1.3×10-7mm3 / Nm). It is used for tool or workpiece surface protection and can effectively extend its service life. These coatings have high hardness, but their poor toughness has always been difficult to solve, resulting in easy cracking and crack propagation, which is far from meeting the requirements of the nuclear power service environment. Therefore, the development of wear-resistant hard coatings with both high strength and high toughness is an urgent problem to be solved in the surface protection engineering of service components in the nuclear power industry and other fields. Summary of the invention
[0003] The present invention provides a Ti-BN high-strength and toughness wear-resistant ceramic coating and a preparation method and application thereof, so as to solve the technical problem in the prior art that the metal coating has high hardness but poor wear resistance and toughness.
[0004] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is as follows:
[0005] A Ti-BN high-toughness wear-resistant ceramic coating, wherein the molecular form of the ceramic coating is TiB x N y , the range of x is 0.09-0.33, the range of y is 1.18-1.2, the atomic proportion of B in the ceramic coating is 3.9-13%, and the volume fraction of nanotwins in the ceramic coating is 45-65%.
[0006] A method for preparing the Ti-BN high-toughness and wear-resistant ceramic coating as described above comprises the following steps:
[0007] S1. After heating the substrate, place it in the vacuum chamber of the DC magnetron sputtering equipment, adjust the vacuum degree, introduce argon gas, make the pressure of the vacuum chamber 0.3-0.5Pa, then turn on the substrate bias to -1000V~-600V, make the argon gas glow discharge, perform glow cleaning, and obtain the substrate;
[0008] S2, introducing argon gas, adjusting the Ti target power, and using magnetron sputtering technology to perform the first deposition, depositing a Ti transition layer on the substrate to obtain a substrate covered with a Ti transition layer;
[0009] S3, introduce argon and nitrogen, open TiB 2 The target and the Ti target are subjected to a second deposition on the substrate covered with the Ti transition layer. During the second deposition, the flow rate of nitrogen is 5.2-7.2 sccm, the substrate bias voltage is -140--80 V, and the high-strength, toughness and wear-resistant ceramic coating is obtained after cooling.
[0010] Preferably, the heating temperature in S1 is 400° C., and the heating rate is 10° C. / min.
[0011] Preferably, the glow cleaning time in S1 is 10-20 minutes.
[0012] Preferably, the power of the Ti target for the first deposition in S2 is 340-480 W, and the flow rate of the introduced argon gas is 20-25 sccm.
[0013] Preferably, the temperature of the first deposition in S2 is 350-480° C., and the time of the first deposition is 5-15 min.
[0014] Preferably, the thickness of the Ti transition layer in S2 is 70-80 nm.
[0015] Preferably, the second deposition of TiB in S3 2 The power of the target is 65-100W, and the power of the second deposition Ti target is 340-480W.
[0016] Preferably, the temperature of the second deposition in S3 is 350-480° C., and the time of the second deposition is 3-5 h.
[0017] An application of the ceramic coating as described above in pump shafts, impellers and / or valve stems of nuclear power rotating parts.
[0018] The relevant parameters of the second deposition in the preparation method of the present invention, such as TiB2 The power of the target and Ti target, the flow rate of nitrogen, the substrate bias, the deposition temperature, etc. are used to control the atomic proportion of B and the volume fraction of nanotwins in the ceramic coating structure. Nanotwins are introduced into the ceramic coating system. Nanotwins are a structure that can simultaneously improve the strength and toughness of the material. The twin interface generated by the twins has an obstruction and absorption effect on the movement of dislocations, and can also increase the propagation path of crack extension, so that the fracture toughness is significantly improved. In ceramic coatings, due to the different bonding properties from metals, the material strength may be increased or plastic deformation may be performed through the breaking and recombination of covalent bonds. Since amorphous structures do not contain grain boundaries and dislocations, amorphization is also an effective way to improve the strength of materials. Amorphous materials themselves do not have a long-range ordered lattice structure, and their atomic arrangement is random. During the stress process, the amorphous phase can absorb stress through local atomic rearrangement. This disorder of atomic arrangement and stress relaxation mechanism usually lead to a lower elastic modulus. Combining amorphous with nanocrystals will make the entire composite material have a higher strength and a lower elastic modulus. By introducing nano-twin structure and amorphous-nanocrystalline structure into the ceramic coating, the coating has both high strength and low elastic modulus, that is, the H / E value is improved, thereby significantly improving the wear resistance of the material.
[0019] Compared with the prior art, the above technical solution has at least the following beneficial effects:
[0020] The Ti-N, BN and Ti-B bonds in the Ti-BN ceramic coating structure of the present invention are high-strength covalent bonds, which ensure the high hardness and wear resistance of the ceramic coating. The high binding energy of these bonds not only gives the coating significant mechanical hardness, but also ensures its chemical stability in high temperature and chemical corrosion environments. On this basis, the twin boundaries of a large number of nano-twin structures (volume fraction up to 45-65%) introduced into the coating can effectively act on dislocation movement, so that crack propagation is hindered, thereby greatly improving the toughness and impact resistance of the material. At the same time, the introduction of the nano-twin structure transforms the wear mechanism of the coating from a combination of abrasive wear, brittle peeling and microcracks to uniform wear, thereby greatly improving the wear resistance of the coating. In addition, by first depositing a Ti transition layer on the substrate and finely controlling the gas flow rate and substrate bias during magnetron sputtering, the uniformity and adhesion of the final coating are ensured, and the prepared metal coating has high hardness and good wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A cross-sectional morphology diagram of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 1;
[0022] Figure 2 A selected area diffraction pattern of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 1;
[0023] Figure 3 A cross-sectional morphology diagram of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 2;
[0024] Figure 4 A selected area diffraction pattern of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 2;
[0025] Figure 5 A cross-sectional morphology diagram of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 3;
[0026] Figure 6 A selected area diffraction pattern of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Example 3;
[0027] Figure 7 A cross-sectional morphology diagram of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Comparative Example 1;
[0028] Figure 8 A selected area diffraction pattern of a Ti-BN high-toughness and wear-resistant ceramic coating provided in Comparative Example 1;
[0029] Fig. 9 The three-dimensional morphology of the worn surface and the wear scar depth curve of the ceramic coating prepared in Example 2 after wear;
[0030] Fig.10 The three-dimensional morphology of the worn surface and the wear scar depth curve of the ceramic coating in Comparative Example 1 after wear;
[0031] Fig.11 This is a cross-sectional SEM image of the wear scar of the ceramic coating prepared in Example 2;
[0032] Fig.12 is a cross-sectional selected area diffraction pattern of the ceramic coating prepared in Example 2;
[0033] Fig.13 for Fig.11 The ITB structure diagram in the middle circle;
[0034] Fig.14 for Fig.13 HTEM image of the ITB structure in . DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A method for preparing a Ti-BN high-toughness wear-resistant ceramic coating comprises the following steps:
[0038] S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum degree in the chamber reaches 2×10 -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 400°C at a rate of 10°C / min;
[0039] S1. After heating the substrate, place it in the vacuum chamber of the DC magnetron sputtering equipment and adjust the vacuum degree of the vacuum chamber to 2×10 -3 Pa, introduce argon gas to make the pressure of the vacuum chamber 0.3Pa, then turn on the substrate bias to -600V to make the argon gas glow discharge, and perform glow cleaning for 10 minutes to obtain the substrate;
[0040] S2, introducing argon gas, adjusting the Ti target power, and using magnetron sputtering technology to perform the first deposition, the deposition temperature is 350° C., the time is 5 min, the power of the Ti target power during the deposition process is 340 W, the flow rate of the introduced argon gas is 20 sccm, and a Ti transition layer with a thickness of 70 nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer;
[0041] S3, introduce argon and nitrogen, open TiB 2 The second deposition was performed on the substrate covered with the Ti transition layer at a temperature of 350°C for 3 hours. During the second deposition, the nitrogen flow rate was 5.2 sccm, the substrate bias voltage was -110 V, and the TiB 2 The power of the target is 65W, and the power of the Ti target is 480W. After cooling, the high-strength, toughness, and wear-resistant ceramic coating is obtained.
[0042] In this embodiment, a Ti-BN high-strength and wear-resistant ceramic coating is prepared. The molecular form of the ceramic coating is TiB 0.09 N 1.19 The atomic proportion of B in the ceramic coating is 3.9%, and its cross-sectional morphology is as follows Figure 1 As shown, the selected area diffraction pattern is Figure 2 As shown, through Figure 2 The diffraction spots from the two (200) planes of the matrix and the twin crystals are integrated to calculate the twin crystal volume fraction, and the nano-twin crystal volume fraction in the ceramic coating is 45%.
[0043] Example 2
[0044] A method for preparing a Ti-BN high-toughness wear-resistant ceramic coating comprises the following steps:
[0045] S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum degree in the chamber reaches 2×10 -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 400°C at a rate of 10°C / min;
[0046] S1. After heating the substrate, place it in the vacuum chamber of the DC magnetron sputtering equipment and adjust the vacuum degree of the vacuum chamber to 2×10 -3 Pa, introduce argon gas to make the pressure of the vacuum chamber 0.5Pa, then turn on the substrate bias to -1000V to make the argon gas glow discharge, and perform glow cleaning for 20 minutes to obtain the substrate;
[0047] S2, introducing argon gas, adjusting the Ti target power, and using magnetron sputtering technology to perform the first deposition, the deposition temperature is 480° C., the time is 15 min, the power of the Ti target power during the deposition process is 480 W, the flow rate of the introduced argon gas is 25 sccm, and a Ti transition layer with a thickness of 80 nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer;
[0048] S3, introduce argon and nitrogen, open TiB 2 The second deposition was performed on the substrate covered with the Ti transition layer at a temperature of 480°C for 5 hours. During the second deposition, the nitrogen flow rate was 5.2 sccm, the substrate bias voltage was -110 V, and the TiB 2 The power of the target is 85W, and the power of the Ti target is 400W. After cooling, the high-strength, toughness, and wear-resistant ceramic coating is obtained.
[0049] In this embodiment, a Ti-BN high-strength and wear-resistant ceramic coating is prepared. The molecular form of the ceramic coating is TiB 0.18 N 1.18 The atomic proportion of B in the ceramic coating is 7.6%, and its cross-sectional morphology is as follows Figure 3 As shown, the selected area diffraction pattern is Figure 4 As shown, through Figure 4The diffraction spots from the two (200) planes of the matrix and the twin crystals are integrated to calculate the twin crystal volume fraction, and the nano-twin crystal volume fraction in the ceramic coating is 65%.
[0050] Example 3
[0051] A method for preparing a Ti-BN high-toughness wear-resistant ceramic coating comprises the following steps:
[0052] S1. Place the pretreated substrate into the vacuum chamber of the DC magnetron sputtering equipment, and start the mechanical pump, molecular pump, etc. to evacuate the chamber; wait until the vacuum degree in the chamber reaches 2×10 -3 When the temperature is below Pa, the substrate is heated and rotated by increasing the temperature to 400°C at a rate of 10°C / min;
[0053] S1. After heating the substrate, place it in the vacuum chamber of the DC magnetron sputtering equipment and adjust the vacuum degree of the vacuum chamber to 2×10 -3 Pa, introduce argon gas to make the pressure of the vacuum chamber 0.4Pa, then turn on the substrate bias to -700V to make the argon gas glow discharge, and perform glow cleaning for 15 minutes to obtain the substrate;
[0054] S2, introducing argon gas, adjusting the Ti target power, and using magnetron sputtering technology to perform the first deposition, the deposition temperature is 400° C., the time is 10 min, the power of the Ti target power during the deposition process is 400 W, the flow rate of the introduced argon gas is 23 sccm, and a Ti transition layer with a thickness of 75 nm is deposited on the substrate to obtain a substrate covered with a Ti transition layer;
[0055] S3, introduce argon and nitrogen, open TiB 2 The second deposition was performed on the substrate covered with the Ti transition layer at a temperature of 400°C for 4 hours. During the second deposition, the nitrogen flow rate was 5.2 sccm, the substrate bias voltage was -110 V, and the TiB 2 The power of the target is 100 W, and the power of the Ti target is 340 W. After cooling, the high-strength, toughness, and wear-resistant ceramic coating is obtained.
[0056] In this embodiment, a Ti-BN high-strength and wear-resistant ceramic coating is prepared. The molecular form of the ceramic coating is TiB 0.33 N 1.2 The atomic proportion of B in the ceramic coating is 13%, and its cross-sectional morphology is as follows Figure 5 As shown, the selected area diffraction pattern is Figure 6 As shown, through Figure 6 The diffraction spots from the two (200) planes of the matrix and the twin crystals are integrated to calculate the twin crystal volume fraction, and the nano-twin crystal volume fraction in the ceramic coating is 55%.
[0057] Comparative Example 1
[0058] The preparation method in this comparative example is similar to that in Example 3, except that the TiB 2 The power of the target is 120 W, and the power of the Ti target is 300 W. The molecular form of the ceramic coating prepared in this comparative example is TiB 0.5 N 1.32 The atomic proportion of B in the ceramic coating is 17.7%, and its cross-sectional morphology is as follows: Figure 7 As shown, the selected area diffraction pattern is Figure 8 As shown, through Figure 8 The diffraction spots from the two (200) planes of the matrix and the twin crystals are integrated to calculate the twin crystal volume fraction, and the nano-twin crystal volume fraction in the ceramic coating is 42%.
[0059] The ceramic coatings prepared in Example 2 and Comparative Example 1 were tested for surface morphology and wear scar depth after wear. The test results are as follows: Fig. 9 and Fig.10 The wear scar of the ceramic coating in Comparative Example 1 is obvious. The maximum wear scar depth of the coating prepared in Example 2 is 0.54 μm, which is much smaller than the maximum wear scar depth of 1.48 μm in the sample of Comparative Example 1. The structural analysis of the sub-surface layer of the ceramic coating after wear in Example 2 is performed, and the cross-sectional SEM image of the wear scar is as follows: Fig.11 , the cross-sectional selected area diffraction pattern is as follows Fig.12 , Fig.11 The ITB structure in the white circle is as follows Fig.13 , Fig.13 The HTEM image of the ITB structure is shown in Fig.14 It can be seen that nano twins still exist in the sub-surface layer of the coating after wear, and the high-stability nano twins maintain high surface hardness. The introduction of nano twin structure changes the wear mechanism of the coating from a combination of abrasive wear, brittle peeling and micro cracks to uniform wear, thereby greatly improving the wear resistance of the coating.
[0060] Example 4
[0061] This embodiment is similar to Embodiment 2, except that the flow rate of nitrogen during the second deposition process in S3 of this embodiment is 6.2 sccm.
[0062] Example 5
[0063] This embodiment is similar to Embodiment 2, except that the flow rate of nitrogen during the second deposition process described in S3 of this embodiment is 7.2 sccm.
[0064] Comparative Example 2
[0065] This comparative example is similar to Example 2, except that the flow rate of nitrogen during the second deposition process described in S3 of this comparative example is 4.2 sccm.
[0066] Comparative Example 3
[0067] This comparative example is similar to Example 2, except that the flow rate of nitrogen during the second deposition process described in S3 of this comparative example is 8.2 sccm.
[0068] Example 6
[0069] This embodiment is similar to Embodiment 2, except that, in S3 of this embodiment, the substrate bias voltage during the second deposition process is -80V.
[0070] Example 7
[0071] This embodiment is similar to Embodiment 2, except that, in S3 of this embodiment, the substrate bias voltage during the second deposition process is -140V.
[0072] Comparative Example 4
[0073] This comparative example is similar to Example 2, except that the substrate bias voltage during the second deposition process described in S3 of this comparative example is -50V.
[0074] Comparative Example 5
[0075] This comparative example is similar to Example 2, except that the substrate bias voltage during the second deposition process described in S3 of this comparative example is -160V.
[0076] The ceramic coatings in Examples 1-7 and Comparative Examples 1-5 were tested for wear resistance. The test results are shown in Table 1.
[0077] Table 1 Wear resistance test of ceramic coatings in Examples 1-7 and Comparative Examples 1-5
[0078]
[0079] The content of B is mainly adjusted by adjusting TiB 2 The target power is realized. The B content of samples from different batches with the same target power will be slightly different due to the influence of working gas pressure, etc., which is within the error range. Under appropriate working gas pressure conditions, the factors affecting the volume ratio of nanotwins are mainly B content, nitrogen flow rate, and bias pressure. Too high or too low nitrogen flow rate and bias pressure will reduce the volume of nanotwins.
[0080] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A Ti-BN high-toughness and wear-resistant ceramic coating, characterized in that: The molecular form of the ceramic coating is TiB x N y , the range of x is 0.09-0.33, the range of y is 1.18-1.2, the atomic proportion of B in the ceramic coating is 3.9-13%, and the volume fraction of nanotwins in the ceramic coating is 45-65%.
2. A method for preparing the Ti-BN high-toughness wear-resistant ceramic coating according to claim 1, characterized in that: The following steps are involved: S1. After heating the substrate, place it in the vacuum chamber of the DC magnetron sputtering equipment, adjust the vacuum degree, introduce argon gas, make the pressure of the vacuum chamber 0.3-0.5Pa, then turn on the substrate bias to -1000V~-600V, make the argon gas glow discharge, perform glow cleaning, and obtain the substrate; S2, introducing argon gas, adjusting the Ti target power, and using magnetron sputtering technology to perform the first deposition, depositing a Ti transition layer on the substrate to obtain a substrate covered with a Ti transition layer; S3, introducing argon and nitrogen, opening the TiB2 target and the Ti target, and performing a second deposition on the substrate covered with the Ti transition layer. During the second deposition, the flow rate of nitrogen is 5.2-7.2 sccm, the substrate bias is -140~-80 V, and the high-strength, toughness and wear-resistant ceramic coating is obtained after cooling.
3. The preparation method according to claim 2, characterized in that: The heating temperature in S1 is 400° C., and the heating rate is 10° C. / min.
4. The preparation method according to claim 2, characterized in that: The glow cleaning time in S1 is 10-20 minutes.
5. The preparation method according to claim 2, characterized in that: The power of the Ti target for the first deposition in S2 is 340-480 W, and the flow rate of the introduced argon gas is 20-25 sccm.
6. The preparation method according to claim 2, characterized in that: The temperature of the first deposition in S2 is 350-480° C., and the time of the first deposition is 5-15 min.
7. The preparation method according to claim 2, characterized in that: The thickness of the Ti transition layer in S2 is 70-80 nm.
8. The preparation method according to claim 2, characterized in that: The power of the second deposition of TiB2 target in S3 is 65-100W, and the power of the second deposition of Ti target is 340-480W.
9. The preparation method according to claim 2, characterized in that: The temperature of the second deposition in S3 is 350-480° C., and the time of the second deposition is 3-5 hours.
10. An application of the ceramic coating according to claim 1 in a pump shaft, an impeller and / or a valve stem of a nuclear power rotating component.
Citation Information
Patent Citations
W-Si-B hard coating and preparation method and application thereof
CN115181948A